Effect of dual particle size (DPS) on dry sliding wear behaviour of LM30/sillimanite composites. (July 2018) - Sharma, Sandeep; Nanda, Tarun; Pandey, O.P.
Abstract: The effect of dual particle size (DPS) reinforcement (fine:coarse in weight ratios of 1:3, 1:1, and 3:1) on wear behaviour of LM30/sillimanite composites is reported. Optical micrographs revealed uniform distribution of particles in the matrix. Al2 Si4 O10 phase was observed using XRD owing to the interfacial reactions of particle with matrix. Further, high nanohardness values of interface revealed sound particle-matrix bonding. The wear resistance of 15 wt.% DPS composites with weight ratio 3:1 improved by 59% over base alloy. In-addition, the results were comparable with the mathematical model and with cast iron used in brake drum applications. SEM-EDS analysis revealed that at low contact pressure, abrasive/adhesive wear mechanism was dominant, whereas at higher contact pressure delamination wear was dominant. Highlights: LM30/sillimanite composites with dual particle size were prepared. The composites with higher wt% fine revealed best wear properties. To improve wear resistance dual particle size reinforced particles should be preferred. The composites can be used as replacement for break drum applications.